SiNext: The next generation sign language - et. al., Shivanshu Bajpai, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In today’s smart world people are using smart assistants that made their life easier than ever before. The only principle in this technology is the human voice which plays a key role in this. If the voice is the future of computing what about those who cannot hear or speak? The hearing and speaking impairment society aren’t able to communicate with it. They can only communicate via sign language. The aim is to create a model that can speak up on behalf of the user to the smart assistants so that they can also communicate with them and they can also take advantage of modern technology like home automation. The model uses 'deeplearn-knn-image-classifier' to classify the images and 'knn.predictClass' to predict the signs. Model accuracy during the testing was 90.25%.